International Migration and Gender Differentials in the Home Labor Market : Evidence from Albania - Mendola, Mariapia; Carletto, Gero (2012)
This paper examines the role of male-dominated international migration in shaping labor market outcomes by gender in migrant-sending households in Albania. Using detailed information on family migration experience from the latest Living Standards Measurement Study survey, the authors find that male and female labor supplies respond differently to the current and past migration episodes of household members. Controlling for the potential endogeneity of migration and for the income (remittances) effect, the estimates show that having a migrant abroad decreases female paid labor supply and increases unpaid work. However, women with past family migration experience are significantly more likely to engage in self-employment and less likely to supply unpaid work. The same relationships do not hold for men. These findings suggest that over time male-dominated Albanian migration may lead to women's empowerment in access to income-earning opportunities at the origin.